Enhancing Financial Literacy Among Non-Financial Employees in the Parenting Tech Industry: A Case Study of PT. Tentang Anak - Suryanto Suryanto; Kartina Natalilova; Annisa Kanti; Nila Pusvikasari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
A lack of understanding regarding the impact of operational activities on financial statements often hinders cash flow efficiency, particularly in fast-paced startup environments. This Community Service (Pengabdian Kepada Masyarakat) activity aimed to enhance the financial literacy of non-financial employees at PT. Tentang Anak through the